Home-based screening for biliary atresia using infant stool colour cards: A large-scale prospective cohort study and cost-effectiveness analysis. (September 2014) - Schreiber, Richard A.; Masucci, Lisa; Kaczorowski, Janusz; Collet, JP; Lutley, Pamela; Espinosa, Victor; Bryan, Stirling
Objective: Biliary atresia (BA), a leading cause of paediatric liver failure and liver transplantation, manifests by three weeks of life as jaundice with acholic stools. Poor outcomes due to delayed diagnosis remain a problem worldwide. We evaluated and assessed the cost-effectiveness of methods of introducing a BA Infant Stool Colour Card (ISCC) screening programme in Canada. Setting and Methods: A prospective study at BC Women's Hospital recruited consecutive healthy newborns through six incrementally more intensive screening approaches. Under the baseline "passive" strategy, families received ISCCs at maternity, with instructions to monitor infant stool colour daily and return the ISCC by mail at age 30 days. Additional strategies were: ISCC mailed to family physician; reminder letters or telephone calls to families or physicians. Random telephone surveys of ISCC non-returners assessed total card utilization. Primary outcome was ISCC utilization rate expressed as a composite outcome of the ISCC return rate and non-returned ISCC use. Markov modelling was used to predict incremental costs and life years gained from screening (passive and reminder), compared with no screening, over a 10-year time horizon. Results: 6, 187 families were enrolled. Card utilization rates in the passive screening strategy were estimated at 60–94%. For a Canadian population, the increase in cost for passive screening, compared with no screening, is $213, 584 and the gain in life years is 9.7 ($22, 000 per life-year gained). Conclusions: A BA ISCC screening programme targeting families of newborns is feasible in Canada. Passive distribution of ISCC at maternity is potentially effective and highly cost-effective.